The Demography of Health and Health Care (second edition) - Pol, Louis G. author. aut Link
XIV, 378 p.
Keywords: "Health demography" has come to play an increasingly important role within the larger field during the past twenty years; the number of health professionals who utilize its methods and materials has grown exponentially. In a thoroughgoing revision of the first edition of this classic text and reference, published by Plenum in 1992, the authors convey the general principles that underlie this applied subdiscipline and demonstrate how the merging of demography and health care impacts on the planning processes of a range of health care organizations.